Romain Rolland correspondence - Rolland, Romain, 1866-1944.
ALS (1938 September 23) from Rolland to Alfred O. Mendel recommending the assistance of Princess Marie Bonaparte and mentioning Charles Baudouin and Pierre Jean Jouve. Includes typewritten transcript.
Typewritten transcript, in part.
Novelist, dramatist, and essayist.
In French.
Forms part of: Sigmund Freud collection.
Keywords: Baudouin, Charles, -- 1893-1963.; Bonaparte, Marie, -- Princess, -- 1882-1962.; Jouve, Pierre Jean, -- 1887-1976.; Mendel, Alfred O. -- Correspondence; Dramatists; Essayists; Novelists